Akytojo betono garso absorbcijos tyrimai - Laukaitis, Antanas; Lasauskas, Vytautas (Journal of Civil Engineering and Management, 1996)
Porous concrete sound absorption investigationLow-density porous concrete can be used as a sound absorbing material. This paper generalizes porous concrete sound absorption investigations.Porous concrete relative wave resistance modulus is longer than air wave resistance W=1 and that is why this material can be ascribed to materials with a high resistance to air flows, i.e. materials with a satisfactory sound absorption.Various thickness porous concrete sample sound absorption coefficients can be calculated according to equations (1), (2), (3), when wave parameter values are determinated (Table 1). Normal sound absorption coefficient measurement results (Fig. 1) show that for 35 mm and thicker samples the coefficient does not vary. It means that the samples apparent resistance (impleance) coincides with the materials wave resistance.The sound absorption coefficient increases (Fig. 2) with a decrease in porous concrete density. The asymmetric average dependency is expressed by a rectilinear curve (Fig. 3). The sound absorption coefficient depends not only on porous concrete density, but also on its nature (Fig. 4). The different sound absorption coefficient values for uniform density porous concrete can be explained by the various structure of porous concrete products, i.e. a change in pore dimensions, their amount and distribution (Fig. 5, Table 2).The production of acoustical slabs has shown that 280350 kg/m3 density porous concrete products are not sufficiently strong. It was therefore decided to increase their density to 460 kg/m3, with the purpose of increasing the sound absorption coefficient by using various special form resonators (cavity-type accelerators).The influence of the cuts on sound absorption is given in Fig. 6 (cut step is 22 mm). Measurements in a reverberation chamber have shown that the sound absorption coefficient value in porous concrete slabs with deeper or complex cuts increases, but it is harder to produce slabs with complex form cuts.It is easier to make a simple form resonator. Reverberated sound absorption for regular form resonators is given in Fig. 7. Porous concrete slab surface acoustical resistance decreases due to cuts and that is why there is an increase in sound absorption coefficients (Fig. 7, 2 and 3 curves).Porous concrete slabs with resonator cuts on both sides can be used in spacious constructions, for noise absorption in industrial premises. In this case, the construction sound absorption coefficient depends on the lay-out of these slabs.Three types of special lay-outs were investigated (Fig. 8, Table 3). Most of the investigated constructions have revertible sound absorption coefficients higher than 1. This is explained by sound diffraction phenomena on the slab edges.The most effective of all the investigated constructions are those where porous concrete slabs with two-sided perforations are hung jointly (Fig. 8, curves 6 and 10). They are effective in the entire distance between the slabs. The reverberation absorption coefficient decreases for all types of constructions (Fig. 8, curves 1 and 2, 5 and 6, 7–10). The special construction sound absorption coefficient can be changed by selecting porous concrete slab lay-out.Article in Lithuanian.First Published Online: 26 Jul 2012